STUDENT RESPONSE TO THE EFFECTIVENESS OF SIMPLE PROPS AS A PHYSICS LEARNING MEDIA IN CHARLES LAW MATERIALS AT SMA UNGGULAN BPPT DARUS SHOLAH JEMBER - Ayu Sulistiyowati; I Ketut Mahardika; Subiki Subiki; Siti Nur Afitah; Lailiyatul Mukarromah; Tia Dwi Riskiyanti (JPF (Jurnal Pendidikan Fisika) Universitas Islam Negeri Alauddin Makassar, 2022)
Student response to the effectiveness of simple props as a physics learning media in charles law materials at SMA Unggulan BPPT Darus Sholah Jember to find out student opinions regarding props used in class. The method used is descriptive statistical method. The instrument of this research used a closed questionnaire. The research subjects were 21 students of 11th grade science class, SMA Unggulan BPPT Darus Sholah Jember. Data analysis technique with validity and reliability test. Based on the results of the validity test that has been carried out, the data as many as 10 questions are declared valid and the reliability test of 0.875 is declared reliable. The results of the average percentage effectiveness of the overall statement amounted to 89,037% classified as very effective. This means that simple props on Charles's law material are very effective as a medium for learning physics.